The Design and Implementation of Scrambling Wavelength Hopping with AWG Router and Optical Switch over Secure WDM Network - Chang, Yao-Tang; Cheng, Hsu-Chih; Lin, Yih-Chuan; Zheng, Yu-Xiang (Proceedings of Engineering and Technology Innovation, 2017)
In current experimental design, by exchanging the optical switch configured in front of arrayed waveguide grating (AWG) router, the wavelength hopping configuration was implemented over wavelength division multiplexing (WDM) network. In addition, in order to enhance the variable wavelength hopping pattern of proposed scheme, the transceiver oscillators were used to trigger the optical switch by a series of random and un-predictable electrical signal. The experiment results proved possible solution of secure WDM network that the wavelength hopping effect was monitored by optical spectrum analyzer (OSA) in optical domain. By using the oscilloscope for monitoring, the results showed the transmitted analogy signal of 10MHzwas extracted correctly by photo-detector while the wavelength hopping is happened